A review on electrodeposition and tribological performance of chromium-based coatings from eco-friendly trivalent chromium baths - Vyacheslav Protsenko (Discover Electrochemistry)
Abstract Electrodeposited chromium coatings are widely recognized for their exceptional tribological properties, including high microhardness, outstanding wear resistance, corrosion protection, and visually appealing surface characteristics. Historically, these coatings were produced using hexavalent chromium (Cr(VI)) electrolytes, which provided high-performance coatings but exhibited a defect-containing microstructure that limited their long-term durability. Additionally, growing environmental concerns and stringent regulatory restrictions on the use of hexavalent chromium, due to its toxicity and environmental hazards, have led to a significant decline in its industrial use. As a result, there has been a shift toward developing more environmentally friendly alternatives, and trivalent chromium (Cr(III)) plating processes have emerged as a promising solution. These processes enable the production of high-performance coatings with refined microstructures, offering enhanced functional properties and being safer for both human health and the environment. This review provides a comprehensive overview of the electrochemical deposition process of chromium-based coatings from Cr(III) electrolytes, focusing on their tribological properties. The review discusses how various electrolysis parameters, such as current density and bath composition, influence the functional properties of the coatings, including microhardness, wear resistance, and corrosion resistance. Additionally, it highlights how these properties can be further improved through process optimization. The review concludes by exploring the future prospects of trivalent chromium electroplating, emphasizing new methodologies and advancements in existing techniques to enhance coating performance and sustainability.